Broadband conversion of visible light to near-infrared emission by Ce3+, Yb3+-codoped yttrium aluminum garnet - Liu, Xiaofeng; Teng, Yu; Zhuang, Yixi; Xie, Junhua; Qiao, Yanbo; Dong, Guoping; Chen, Danping; Qiu, Jianrong (Optics letters, 2009)
We show that Ce(3+) can be an efficient sensitizer for Yb(3+) in the host lattice of yttrium aluminum garnet (YAG). With blue-light excitation to induce the 4f-->5d transition of Ce(3+), characteristic near-IR emission of Yb(3+) due to transition of (2)F(5/2)-->(2)F(7/2) peaking at 1030 nm is generated as a result of energy transfer from Ce(3+) to Yb(3+). The result of spectral evolution with temperature indicates that the efficiency of energy transfer is enhanced owing to thermal effect. This evidence implies that the phonon-assisted process participates in the downconversion of YAG: Ce(3+), Yb(3+).